2016
DOI: 10.1111/psyp.12607
|View full text |Cite
|
Sign up to set email alerts
|

Attention‐dependent sound offset‐related brain potentials

Abstract: When performing sensory tasks, knowing the potentially occurring goal-relevant andirrelevant stimulus events allows the establishment of selective attention sets, which result in enhanced sensory processing of goal-relevant events. In the auditory modality, such enhancements are reflected in the increased amplitude of the N1 event-related potential (ERP) elicited by the onsets of task-relevant sounds. It has been recently suggested that ERPs to task-relevant sound offsets are similarly enhanced in a tone-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 45 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…Although the between-deflection intervals were very similar to those observable in a typical onset-related waveform, the waveform itself was uniformly delayed by about 50 ms (i.e., the P1 peaked at about 100 ms, and the N1 at about 150 ms after the start of the offset transient). Interestingly, the waveform was most prominently observable at temporal sites (Horváth, 2016). Because of its topographical distribution and timing, it was suggested that the offset-related waveform may be analogous to the T-complex rather than to the typical onset-related waveform, in which the fronto-central negativity at 100 ms is the most pronounced.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the between-deflection intervals were very similar to those observable in a typical onset-related waveform, the waveform itself was uniformly delayed by about 50 ms (i.e., the P1 peaked at about 100 ms, and the N1 at about 150 ms after the start of the offset transient). Interestingly, the waveform was most prominently observable at temporal sites (Horváth, 2016). Because of its topographical distribution and timing, it was suggested that the offset-related waveform may be analogous to the T-complex rather than to the typical onset-related waveform, in which the fronto-central negativity at 100 ms is the most pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…Further ERP components overlapping the N1 and P2 can be found in different stimulation and task arrangements (Näätänen and Picton, 1987). In tasks requiring sound-based decisions, the deflection descriptively labeled as N1 may actually receive contributions from the processing negativity (PN, Näätänen et al, 1978; or negative difference -Nd, see Hansen and Hillyard, 1980) or N2 (Horváth, 2016) components. Whereas PN probably reflects processing related to the matching of the incoming sound to a voluntarily maintained auditory template, an attentional trace (Näätänen, 1982(Näätänen, , 1990, N2 may reflect the evaluation of the stimulus in terms of the given task (Ritter et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations